Factores que influyen en la evaluación numérica de los estudiantes de la unidad educativa Luis Ulpiano de la Torre. - Ubidia, Pamela K. (2022)
Education transforms, but it does not always improve, because there are those who end their school life with insecurities, fear and even limits of what they can be or do, with many concepts learned by heart that they cannot apply and believing that good grades guarantee a successful future in life. These criteria that are established in the students, are anchored to a variable of education, the numerical evaluation. As if learning were exclusively related to approval and forgetting learning. The reasons are not based on teachers and students, but on psychological, historical, social, cultural and economic factors that conditioned the existence and validity of the evaluation in its numerical form. A main actor that appeared in this research was the traditional exam-, instrument used for the ease it presents to measure the memorization of concepts and the settlement of a note. Detaching the evaluation and learning criteria and linking others to the evaluative practice, such as: measuring, classifying, competing and even sanctioning. The students, for their part, proposed evaluation methods other than written test, because they do not consider it to be an effective way of assessing their learning. Teachers were also open to implementing different assessment method, even though they recognized the mechanical application of tradition. The evaluation cannot be based on standarized tests, it must build a broader vision of the students, his context, his ways of learning and his abilities.